2018
DOI: 10.1016/j.sapharm.2017.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Professional identity development: Learning and journeying together

Abstract: Opportunity for collaboration and exchange can positively influence development of students' professional outlook and values. However, careful management of group working is required, in order to create a mutually supportive environment wherein students feel able to interact, share and develop together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The results regarding Scenario 4 (i.e., responsibility undertaking) showed that more experienced professionals seemed more risk-averse, which can be attributed to their increased exposure to teamwork that develops values that are oriented to the benefit of others, creates a sense of responsibility, and fosters an ethos of mutual support [83]. In addition, it is expected that professionals with more working experience have undertaken supervisory and managerial roles that are typically followed by a sense of accountability [84,85].…”
Section: Discussionmentioning
confidence: 99%
“…The results regarding Scenario 4 (i.e., responsibility undertaking) showed that more experienced professionals seemed more risk-averse, which can be attributed to their increased exposure to teamwork that develops values that are oriented to the benefit of others, creates a sense of responsibility, and fosters an ethos of mutual support [83]. In addition, it is expected that professionals with more working experience have undertaken supervisory and managerial roles that are typically followed by a sense of accountability [84,85].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest to this study is the observation by Skorikov & Vondracek, that human motivation also has a role to play professional identity formation: '…a professional identity is represented by a "complex structure of meanings in which the individual links his or her motivation and competencies with acceptable career roles' 5 Research into pharmacy student professional identity development has largely focused on the collective level, as it reports on the importance of role models, interactions with practicing professionals and experiential education. [6][7][8] However, Dall'Alba 9 highlights the importance of the individual level and describes the importance of developing a sense of who the student is becoming, through an ontological, as well as an epistemological approach to teaching aspiring professionals. Such an approach should create opportunities for students to think, act and feel like a professional.…”
Section: Introductionmentioning
confidence: 99%
“…Second, several programs sought to understand how particular pedagogical practices contributed to PIF, for example, reflective essays,29 coaching,58 socialization activities including placements,47 and facilitated discussions with academics 59. The contributions of these programs to the students’ formation of professional identities were examined through questionnaires,58 evaluation of reflective essays,29 or interviews (group and individual) 59. Some of these evaluations were informed by professional identity theory, for example, social identity theory47 and Baxter-Magolda’s self-authorship theory 29.…”
Section: Resultsmentioning
confidence: 99%